2012
DOI: 10.1038/bjc.2012.388
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of live/apoptotic circulating tumour cells as predictive marker of response to Sunitinib in metastatic renal cancer

Abstract: Background:Recently, we developed an apoptotic assay for expanding the monitoring capabilities of the circulating tumour cells (CTC) test during therapy. An automated platform for computing CTCs was integrated with a mAb (M30) targeting a neoepitope disclosed by caspase cleavage at cytokeratin 18 in early apoptosis; we showed that live CTCs were associated with progression, consistent with enhanced cell migration and invasion. The test was first applied here to mRCC.Methods:Live/apoptotic CTCs changes were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 38 publications
5
49
0
Order By: Relevance
“…The prognostic role of circulating tumour cells (CTCs) have been demonstrated in breast cancer [26] and other neoplasms, while their significance in RCC is still debated. In an exploratory study conducted at our Institution, a fluctuation of CTC values has been observed in RCC patients during treatment with sunitinib, and the balance of live and apoptotic cells appeared to correlate with longer disease control [27].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic role of circulating tumour cells (CTCs) have been demonstrated in breast cancer [26] and other neoplasms, while their significance in RCC is still debated. In an exploratory study conducted at our Institution, a fluctuation of CTC values has been observed in RCC patients during treatment with sunitinib, and the balance of live and apoptotic cells appeared to correlate with longer disease control [27].…”
Section: Discussionmentioning
confidence: 99%
“…Statistical Analysis-The cumulative changes of live and apoptotic CTCs were expressed as described previously (27) by the parameter ⌬AUC; the detected numbers of M30-negative and M30-positive CTCs were separately plotted in relation to time, and the area under the curve (AUC) of longitudinal graphs was calculated (by the trapezoidal rule) following a procedure that is commonly adopted to evaluate cumulative changes of serological tumor markers. The difference between live and apoptotic CTC concentration-time area was calculated in all patients according to Equation 1,…”
Section: Methodsmentioning
confidence: 99%
“…We recognize and acknowledge in the manuscript that detection of all apoptotic CTCs may not be necessary to demonstrate clinical response to therapy. Instead we propose, as previously stated in the original manuscript, that the detection of any apoptotic cells within the CTC population is a potential indicator of therapy response, as has been elegantly demonstrated by previous work by Rossi et al (3,4). Building on their previous studies, this Communication has afforded Rossi et al the opportunity to publish a small amount of additional data that demonstrates (not surprisingly) that a 2-marker apoptosis assay (M-30/gH2AX) may have more utility than M-30 alone on the CellSearch, at least in spiked samples.…”
mentioning
confidence: 96%